2006
DOI: 10.1111/j.1469-0691.2005.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of Eucalyptus globulus leaf extract on pathogenic bacteria isolated from specimens of patients with respiratory tract disorders

Abstract: The antibacterial activity of Eucalyptus globulus leaf extract was determined for 56 isolates of Staphylococcus aureus, 25 isolates of Streptococcus pyogenes, 12 isolates of Streptococcus pneumoniae and seven isolates of Haemophilus influenzae obtained from 200 clinical specimens of patients with respiratory tract disorders. MIC50s for these species were 64, 32, 16 and 16 mg/L, respectively; MIC90s were 128, 64, 32 and 32 mg/L, respectively; and MBCs were 512, 128, 64 and 64 mg/L, respectively. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 5 publications
3
48
1
1
Order By: Relevance
“…These results are almost similar to those shown by other works on the antimicrobial activity of essential oil of E. globulus leaves as well as those of similar species [14,[21][22][23][24][25][26][27][28][29] , and confirms its traditional uses [26,30,31] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are almost similar to those shown by other works on the antimicrobial activity of essential oil of E. globulus leaves as well as those of similar species [14,[21][22][23][24][25][26][27][28][29] , and confirms its traditional uses [26,30,31] .…”
Section: Discussionsupporting
confidence: 90%
“…A suspension of each sample tested microorganism diluted prior to 10-1, 10-2 and 10-3 (1 mL of 10 8 cells /mL) was spread on a solid agar medium in Petri dishes (Mueller-Hinton agar). Filter paper discs (6 mm in diameter) were soaked in 13 毺L of the essential oil and placed on the inoculated plates and allowed to dry for 15 min, then incubated at 37 曟 for 24 h. The diameters of the inhibition zones were measured in millimeters [19] .…”
Section: Antimicrobial Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…All growth parameters were best with the group 4 which was treated with Respofeed. The present study was akin to the findings of [20,21,22,23], who reported that volatile oils helps to treat CRD, improve body weight gain and reduces lesion scores. …”
supporting
confidence: 56%
“…The effect of volatile oils in clearing of respiratory signs was investigated by [17,18,19,20,21,22] . [23] were infected with MG and no treatment was provided to the bird (Table 1 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%